The Political Perception Of Youth: Where Are We Heading To? - Meheri Tamanna (Jurnal Akta, 2018)
Youth in politics can be a creative force, a dynamic source of innovation which in turn brings positive changes in political systems. But today’s youth is neither deeply apathetic nor unconventionally engaged in mainstream politics due to its complex nature. This decreasing level of youth participation in politics not only endangers the quality of leadership but also jeopardizes the democracy of tomorrow. By using qualitative and quantitative data this study explored the trend of youth engagement and their disconnection with the current political systems. This study aimed to observe how the youth is unbundling the traditional concept of state power and identify the reasons for their non-engagement in politics which eventually challenges the political system of Bangladesh.Keywords: Engagement, Democracy, Politics, Young population, Leadership.